Secondary School EFL Teachers’ Perception of ICT Use in Learning and Teaching: A Case Study in Greater Jakarta - Pardede, Parlindungan (JET (Journal of English Teaching), 2020)
The influx of ICT tools into EFL classrooms has provided an increasing range of possible solutions for refining teaching and learning inputs, processes, and outcomes, and their use can benefit students and teachers. However, ICT implementation in the learning process is affected by various factors, among which teachers’ perception is the most significant. This study aimed at investigating teachers’ perceptions of ICT use in EFL learning activities. To attain the aim, data as collected by asking 32 EFL teachers from various junior and senior high schools in Greater Jakarta to fill in a questionnaire consisting of 60 closed-ended questions. To triangulate and elaborate the quantitative data, 5 open-ended questions were asked to 8 of the participants selected as the interviewees. The results indicate that the teachers had a good level of perception of ICT use in EFL learning and teaching activities. The majority of them had integrated ICT in their EFL classrooms. Regarding the issues related to facilities and technical expertise they sometimes encountered, they either asked for help from technicians or colleagues. Many of them also agreed with the importance of attending training to enhance their skills in using ICT in learning and teaching.